In Vitro Red Blood Cell Segregation in Sickle Cell Anemia - Clavería, Viviana; Connes, Philippe; Lanotte, Luca; Renoux, Céline; Joly, Philippe; Fort, Romain; Gauthier, Alexandra; Wagner, Christian; Abkarian, Manouk (Frontiers in Physics, 2021)
Red blood cells in sickle cell anemia (sRBC) are more heterogeneous in their physical properties than healthy red blood cells, spanning adhesiveness, rigidity, density, size, and shape. sRBC with increased adhesiveness to the vascular wall would trigger vaso-occlusive like complications, a hallmark of sickle cell anemia. We investigated whether segregation occurs among sRBC flowing in micron-sized channels and tested the impact of aggregation on segregation. Two populations of sRBC of different densities were separated, labeled, and mixed again. The mixed suspension was flowed within glass capillary tubes at different pressure-drops, hematocrit, and suspending media that promoted or not cell aggregation. Observations were made at a fixed channel position. The mean flow velocity was obtained by using the cells as tracking particles, and the cell depleted layer (CDL) by measuring the distance from the cell core border to the channel wall. The labeled sRBC were identified by stopping the flow and scanning the cells within the channel section. The tube hematocrit was estimated from the number of fluorescence cells identified in the field of view. In non-aggregating media, our results showed a heterogeneous distribution of sRBC according to their density: low-density sRBC population remained closer to the center of the channel, while the densest cells segregated towards the walls. There was no impact of the mean flow velocity and little impact of hematocrit. This segregation heterogeneity could influence the ability of sRBC to adhere to the vascular wall and slow down blood flow. However, promoting aggregation inhibited segregation while CDL thickness was enhanced by aggregation, highlighting a potential protective role against vaso-occlusion in patients with sickle cell anemia.